Dentigerous cyst with ameloblastic transformation - Klinger de Souza Amorim; Anne Caroline Gercina Carvalho Dantas; Allen Matheus da Silva Nascimento; Monique Lorem Souza Rios; Ricardo Luiz Cavalcanti de Albuquerque Júnior; Liane Maciel de Almeida Souza (Editorial Ciencias Médicas, 2020)
Introduction: Dentigerous cysts are caused by the separation of the follicle remaining around the crown of unerupted teeth. They are the most common type of developmental odontogenic cyst. Their growth is slow and asymptomatic, and they may reach large dimensions. Objective: Report a surgical case of dentigerous cyst with ameloblastic transformation. Case presentation: A case is presented of a black female 14-year-old patient. Radiography revealed an area of unilocular radiolucency with well-defined margins enveloping the crowns of teeth 48 and 47. Treatment was a combination of enucleation and curettage of the lesion, exodontia of the teeth and cryotherapy to devitalize the surrounding bone. Eventual histopathological examination confirmed the diagnosis of dentigerous cyst with ameloblastic transformation. Conclusions: At the time when the report was written, the patient had been followed up for three years after surgery, showing bone neoformation and no recurrence of the lesion.